Pengembangan Panduan Pelatihan Empati Menggunakan Teknik Sinema Edukasi untuk Mencegah Perilaku Bullying Siswa Sekolah Menengah Pertama - Cahyaningrum, Vesti Dwi; Handarini, Dany Moenindyah; Simon, Irene Maya (Jurnal Kajian Bimbingan dan Konseling, 2018)
This study aimed to develop a training guide of empathy attitude skills as prevention of bullying behavior on junior high school students. The method was a research and development model. The subjects of the research were guidance and counseling experts; educational technology expert; and school counselors. The instrument was the empathy attitude skill scale for students; expert assessment instruments and counselor assessment instruments. Data from the assessment results of guidance and counseling expert; educational technology expert; and three school counselors in three different schools in Malang City showed that the developed products were acceptable and feasible to be used to improve empathy skills as prevention of bullying behavior of junior high school students.